Efficient Cu(I) acetate‐catalyzed cycloaddition of multifunctional alkynes and azides: From solution to bulk polymerization. Issue 2 (17th November 2013) - Sandmann, Benedict; Happ, Bobby; Hager, Martin D.; Vitz, Jürgen; Rettler, Erik; Burtscher, Peter; Moszner, Norbert; Schubert, Ulrich S.
ABSTRACT: "Click" chemistry is an effective and commonly used technique in polymer chemistry for the synthesis and modification of polymers. In this study, the bulk polymerization of multifunctional alkynes and azides was achieved by the copper(I)‐catalyzed alkyne–azide 1, 3‐dipolar cycloaddition. The influence of different catalyst systems on the polymerization kinetics of the "click"reaction were evaluated by differential scanning calorimetry. Surprisingly, Cu(I) acetate showed the most efficient catalytic behavior among the applied Cu(I) salts. The polymerization kinetics in solution were investigated by 1H NMR spectroscopy and size exclusion chromatography. According to the 1H NMR investigation the copper(I)‐catalyzed cycloaddition follows a second‐order kinetics with external catalysis. Additionally, the mechanical properties of the resulting polymers were investigated by depth sensing indentation. Thereby the polymerizations of the alkyne tripropargylamine with the azides 1, 3‐bis(azidomethyl)benzene and 1, 4‐bis(azidomethyl)benzene resulted in mechanical hard materials. Furthermore, the combination of the alkynes tripropargylamine and di(prop‐2‐yn‐1‐yl) isophorone dicarbamate and polymerization with 1, 2‐bis(2‐azidoethoxy)ethane resulted in high indentation moduli. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 239–247 Abstract : The solvent‐free copper‐catalyzed alkyne azide 1, 3‐cycloaddition technique can be used for the preparation of different constructions of polymers. By using multifunctional alkynes and azides it is possible to synthesize materials with notable mechanical properties that make them interesting for different applications.